Total force of pinch and grasp by hand postures - Lee, Kyung Sun; Jung, Myung Chul (Advances in Intelligent Systems and Computing, 2018)
The aim of this study was to measure the total force of pinch and grasp by various hand postures of pinching with two fingers (2P), three fingers (3P), four fingers (4P), and five fingers (5P), and power grip (5G). Male graduate and undergraduate students participated in the experiment. The pinch and grasp forces were measured using a pressure measurement system with a pad. The pad of the body pressure measurement system was attached to the object using double-sided tape. The participants picked up the objects using the hand posture required by the experimenter. The participants were asked to lift the object to approximately shoulder height and maintain the posture for 3 s. The results of ANOVA applied to the total forces on the thumb, index, middle, ring, and little finger, which indicated that the main effects of the hand posture (p < 0.0001). The total force on the thumb increased as the number of fingers used increased. However, the total force on the index finger decreased as the number of fingers used increased, except for the 5G hand posture. In conclusion, the hand posture difference was also evident in the distribution of the individual finger force.
Keywords: External force; Hand posture; Number of fingers; Pinch and grasp; Pressure measurement system; Shoulder heights; Total force; Undergraduate students; External force; Hand postures; Pinch and grasp; Total force